Research on Static Tension Ratio Characteristic of Double-Vessel Friction Hoist System Components - Xie Lirong; Ge Laifu; Kong Jun; Cheng Jing (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Double-vessel multi-rope friction hoist system, of which the lifting, starting, running, and braking must meet the safety conditions in operation. Non-skid safety boundary conditions were originally determined by Euler’s formula. In order to avoid the complex task of check and check-again calculation in the friction hoist system design. In this research, static tension ratio c, which was closely bonded with anti-skid design was directly brought into the analysis and research on the system. As a result, characteristic of static tension ratio c of component quality of friction hoist system was found, which offers a simple, sound and reliable theoretical foundation for the anti-skid and optimization of system configuration.